Determinan Keputusan Pembelian Ulang Berbasis Store Atmosphere, Kualitas Pelayanan Dan Promosi Di Richeese Factory Jatinangor Town Square (JATOS) Sumedang - Jaka Sudewa; Tribowo Rachmat Fauzan; Afif Nur Rokhman; Puspa Rini; Ikhsan Amar Jusman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This purpose of this study is to analyze more deeply the impact of store atmosphere, service quality and promotion on repurchase decisions at Richeese Factory Jatinangor Town Square (Jatos) Sumedang outlets. This research applied quantitative methods and with regression analysis using IBM SPSS version 22. The author uses primary data, which is data collected directly from respondents. The accidental sampling technique was used for sampling and obtained 90 respondents. This study uses several stages of testing, including validity test, reliability tests, classic assumption test, multiple linear regression analysis and also coefficient of determination test. The results of this study show that the store atmosphere (X1), service quality (X2) and promotion (X3) have a significant effect on repeat purchase decisions (Y).repurchase decisions are influenced by store atmosphere, service quality and promotion by 62.5% and the remaining 37.5% is influenced by other factors. This study can be a reference material for business people to design and establish effective and efficient marketing policies. The results of this study also contribute to the development of science and input of Richeese Factory Management to focus more on developing product targeting the millennial generation.